2021
DOI: 10.1017/s1537592721002024
|View full text |Cite
|
Sign up to set email alerts
|

Crisis, Resilience, and Civic Engagement: Pandemic-Era Census Completion

Abstract: How do economic shocks and financial resilience shape civic engagement, especially for the economically insecure? I turn to the early months of the coronavirus pandemic for insights. In April 2020, with more than 23 million adults unemployed, the US government asked residents to participate in the constitutionally mandated decennial census. I test how variations in income shocks from the shutdown and sources of financial resilience predict disparities in census completion, a civic act designed to minimize part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Unlike voting, which may represent self-interested political action, Vigdor (2004) posited that Census completion is a form of individual political engagement that benefits the larger community. Unlike voting, all U.S. residents are required to complete the Census and the process is designed to require limited resources (Denny, 2022), but completion of the return reflects a willingness to engage with government (Desouza & Bhagwatwar, 2012). As the 2020 Census was being fielded as the pandemic began and COVID-19 funds were being launched, we used county-level 2010 Census return rates.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike voting, which may represent self-interested political action, Vigdor (2004) posited that Census completion is a form of individual political engagement that benefits the larger community. Unlike voting, all U.S. residents are required to complete the Census and the process is designed to require limited resources (Denny, 2022), but completion of the return reflects a willingness to engage with government (Desouza & Bhagwatwar, 2012). As the 2020 Census was being fielded as the pandemic began and COVID-19 funds were being launched, we used county-level 2010 Census return rates.…”
Section: Methodsmentioning
confidence: 99%
“…Several factors, such as financial literacy, planning, and self- efficacy, have been identified as determinants in predicting financial resilience (Ervina et al, 2020). However, previous studies on the determinants of financial resilience have been predominantly focused on investigations at specific levels, such as the organizational level (Merdiaty et al, 2021;Nkundabanyanga et al, 2019), household level (McKnight & Rucci, 2020) community level (Denny, 2022), and student level (Prameswari, 2020). Many studies have utilized the perspective resilience of finance at the individual level, including from the viewpoint of the adult age group (Hassan et al, 2018), Productive age group (Lyons et al, 2020), the workers (Setyorini et al, 2021), and the middle-aged (Bialowolski et al, 2022).…”
Section: Financial Resiliencementioning
confidence: 99%
“…Research on financial resilience has been conducted from various perspectives, including financial resilience for organizations (Merdiaty et al, 2021;Nkundabanyanga et al, 2019), financial resilience at the household level (McKnight & Rucci, 2020), and financial resilience at the community level (Denny, 2022) several researchers have conducted investigations at the individual level, particularly regarding the determinants of financial resilience. Among the individual classes that have been studied are the productive age groups (Lyons et al, 2020), adulthood (Hassan et al, 2018), and the workers (Setyorini et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have focused on citizens' engagement in several ways. For example, Denny [27] suggested that civic engagement, such as residents taking an interest in local disasters, trust between residents, and a sense of belonging to the community, could help overcome the effects of disasters.…”
Section: Civic Engagement In Turbulent Timesmentioning
confidence: 99%